2013
DOI: 10.1109/tdei.2013.6508760
|View full text |Cite
|
Sign up to set email alerts
|

Study on broadband loss characteristics of oil-immersed papers for fast transient modeling of power transformer

Abstract: In order to complete the broadband simulation model of power transformer, and establish a systematic and complete model for studying fast transient interaction between transformer and power system, the frequency dependent characteristics of dielectric losses in power transformer were investigated. Several typical insulation structures in power transformers were considered and measuring techniques determined to study the dielectric losses. Frequency dependent dielectric losses in the range of 10-10 7 Hz were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Here, ε' is the real component of permittivity and ε" is the imaginary component of the permittivity. A first-order Debye model function, as shown in Equation (2), was used to obtain complex permittivity [21].…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, ε' is the real component of permittivity and ε" is the imaginary component of the permittivity. A first-order Debye model function, as shown in Equation (2), was used to obtain complex permittivity [21].…”
Section: Simulation Setupmentioning
confidence: 99%
“…Therefore, it is necessary to identify if sensors installed at these positions are still the most sensitive when the PD sources are inside the winding. The sensors corresponding to these locations are sensors 1, 4, 5, 8, 9, and 12 on the HV side and sensors 13,16,17,20,21, and 24 on the MV/LV side. From Table 2, it can be observed that most of these sensors have four PD sources from which they receive signals that are below the threshold.…”
Section: Hv and Mv/lv Sensorsmentioning
confidence: 99%
“…is regarded as the reference temperature (different operating or thermal aging temperature), t ref (t) is the time (hours) required for the chemical reaction to reach a certain aging degree at the temperature of T ref (T). Review the Arrhenius theory, which is utilized to interpret the variation law between chemical reaction rate and reaction temperature [17,18] as is shown in Equation (16).…”
Section: A Modified Aging Kinetics Model For Aging Condition Predictimentioning
confidence: 99%
“…In literature [14,15], the integral value of the FDS curve is computed and applied as the feature parameter for achieving the above goal. In addition, the equivalent circuit model that is capable of analyzing the corresponding aging condition is also reported, such as the Cole-Cole model [16], the Havriliak-Negami model [17], the Davidson-Cole model [18], and the Dissado-Hill model [19]. However, it is a fact that the contribution of the aging condition on measured FDS data could be easily covered by the moisture effect [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One is based on extracting the feature parameters 2 of 17 from the dielectric response curves [11,[15][16][17]. The other is realized by establishing the equivalent circuit model to extract the feature parameters of dielectric response property [18,19]. The above methods could extract the feature parameters, reflecting the moisture inside oil-immersed insulation.…”
Section: Introductionmentioning
confidence: 99%